Multislice CT angiography of fenestrated endovascular grafts: A pictorial essay - Sun, Zhonghua; Mwipatayi, B.; Allen, Yvonne; Hartley, D.; Lawrence-Brown, M. (Springer, 2008)
Objective: The purpose of this article is to provide 2D and 3D imaging appearances of fenestrated endovascular repair of abdominal aortic aneurysms (AAA) based on multislice CT angiography.Methods and Results: 14 patients with AAA unsuitable for conventional endovascular repair undergoing fenestrated endovascular grafts were included in the study. Post-fenestration multislice CT data were reconstructed for generation of VIE images of aortic artery ostia and fenestrated vessel stents, in addition to routine 2D axial and multiplanar reformatted images. This includes visualization of intraluminal appearance of fenestrated vessel stents and measurement of the length of stents protruding into the aortic lumen. Various fenestrations were performed in 45 aortic branches with 36 stents deployed into the fenestrated vessels. CT VIE was found superior to conventional 2D images in the visualization and characterization of intraluminal appearance of fenestrated vessel stents.Conclusion: While 2D axial images are routinely used for follow-up of fenestrated endovascular grafts, some types of 3D reconstructions are recommended for inclusion in the imaging follow-up as they enhance endovascular specialists' understanding of the fenestrated procedures by providing additional information.